A Comparative Study on Effect of Small Group Discussion versus Didactic Lectures among Medical Students - Chithuru Vishnu Priya; Obbu Kiran Kumar; Phanindra Dulipala; Ravi Kiran, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Small group discussion stimulates collaboration and in-depth discussion for application and transfer of knowledge, known as collaborative learning. This study aimed to compare the effect of small group discussion and conventional didactic lecture teaching learning methods. Methods: A comparative study was conducted among final MBBS part 1 students for a period of one month. A total of 128 students were included in the study. All the students were divided into 2 groups. Didactic lecture was given to one group and small group discussion was conducted to another group. Post test was conducted to assess and scores were compared pre and post in both groups. Results: Of 128 students, 35% (45) were males and 65% (83) were females. In the post test, for a maximum score of 20 marks, the mean score of students subjected to didactic lecture was 13.1 ± 2.02 (66%) and that of small group discussion was 12.34 ± 2.08 (62%) and association between the two variables was found to be statistically significant. There is also significant difference in the performance of students of didactic lectures and that of small group discussion in the recall test with a mean score of 11.23 ± 2.65 (56%) and 12.28 ± 2.56 (61%) respectively Conclusion: The knowledge from small group discussion is more long lasting and has better recall. So small group discussion can be adopted as another alternative teaching modality which can bring better output among the medical students.